The Encyclopedia of the Dog - Fogle, Bruce; Photography by Morgan, Tracy (New York DK Publishing, 2012)
"This magnificent volume is the most comprehensive exploration of the canine world ever published. With detailed descriptions of more than 420 breeds and varieties of dogs from around the world, The Encyclopedia of the Dog also includes an entertaining look at canines throughout history as well as invaluable practical advice."--
Include Color Illustration
Keywords: Dog breeds -- Dog